Tailoring polymer electrolytes with PVA for improved performance in electrical double layer capacitors - Hamsan, M.H.; Hama, Peshawa O.; Aziz, Shujahadeen B.; Hadi, Jihad M.; Ahmed, Mohammed B.; Abdullah, Ranjdar M.; Sadiq, Niyaz M.; F. Z. Kadir, Mohd (Journal of industrial and engineering chemistry (Seoul, Korea), 2025)
[Display omitted] In this work, solid polymer electrolytes (SPEs) were synthesized through solution casting, employing polyvinyl alcohol (PVA) as polymer hosts and sodium thiocyanate (NaSCN) for ion transport. Glycerol was incorporated to enhance ionic conduction. The conducted FTIR results establish that glycerol can dissociate more salts. The band associated with SCN anion decreased in intensity and broadened. The ionic conductivity was determined through electrochemical impedance spectroscopy (EIS). The value of ε’ is about twice that of ε’’ value, which is the subject of enormous scientific debate. The AC conductivity spectrum reveals dissimilar regions endorsed to the contributions of electrode polarization and DC conductivity. The ion fraction and its contributions were determined using transference number measurement (TNM), with ion contributions reaching 0.93. The electrolyte exhibited electrochemical stability up to 2.67 V. Charge transfer via Faradaic processes was not observed at the electrode–electrolyte interface, as indicated by CV measurements. The triangular shape of the galvanostatic charge–discharge (GCD) diagram supports capacitive behavior rather than redox reactions, with a specific capacitance of 40F/g. The regular power and energy densities of the electric double-layer capacitors (EDLCs) were estimated as 1255.2 W/kg and 5.5 Wh/kg, respectively, over 1,500 cycles.